Inhibitory potential of EGCG on Streptococcus mutans biofilm: A new approach to prevent Cariogenesis. (June 2020) - Hairul Islam, Mohamed Ibrahim; Arokiyaraj, Selvaraj; Kuralarasan, M.; Senthil Kumar, Venugopal; Harikrishnan, Pandurangan; Saravanan, Subramanian; Ashok, Ganapathy; Chellappandian, Muthiah; Bharanidharan, Rajaraman; Muralidaran, Senguttuvan; Thirugnanasambantham, Krishnaraj
Abstract: Dental caries is a common cause for tooth loss and Streptococcus mutans is identified as the etiologic pathogen. This study evaluates the inhibitory potential of Epigallocatechin gallate (EGCG) on S.mutans glucansucrase enzyme and its biofilm. Glucansucrase binding and the inhibitory potential of EGCG was validated using AutoDock tool and enzyme inhibitory assay. Biofilm inhibitory potential was also confirmed using Scanning Electron Microscopic (SEM) analysis in human tooth samples. Molecular docking revealed that EGCG interacted with GLU 515 and TRP 517 amino acids and binds to glucansucrase. SEM analysis revealed inhibition of S.mutans biofilm by various concentrations of EGCG on surfaces of tooth samples. Bioinformatics and biological assays confirmed that EGCG potentially binds to the S. mutans glucansucrase and inhibits its enzymatic activity. Enzymatic inhibition of glucansucrase attenuated biofilm formation potential of S. mutans on tooth surface. Thus, we conclude that EGCG inhibitory potential of S. mutans biofilm on the tooth surface is a novel approach in prevention of dental caries. Highlights: Bioinformatics analysis revealed glucansucrase enzyme binding potential of EGCG. EGCG inhibited glucansucrase enzyme activity. SEM analysis revealed EGCG inhibited S.mutans biofilm on surfaces of tooth.